Practices and perceptions of the politics-administration dichotomy in Malawian local government - AL Chiweza; Y Msiska (Journal of Public Administration and Development Alternatives, 2020)
Drawing from survey data and key informant interviews of local government councils in Malawi, this article investigates the nature of the relationship between politically elected and appointed officials as well as the perceptions of the roles of political leaders and administrators in local government policy-making and implementation process. It notes that an efficient local government system requires a good linkage and crossing-point between the political and administrative leadership to ensure that policies are formulated and implemented effectively. The article reveals that in the midst of bureaucratic dominance, the complementarity partnership model is the most preferred by both elected members and administrators. However, this article finds that a significant number of administrators show some ambivalence towards leaving policy-making to elected members alone. Also, it reveals that a significant number of respondents recognize policy implementation to be within the exclusive purview of appointed public administrators. This means that the partnership model is seen to have a strong empirical logic among practicing local government administrators and elected members, thereby signifying their support for interconnectedness as well as the potential strengths of integrating politics and administration in policy development and implementation.